IMPLEMENTING BACKWARD SPELLING QUIZ IN TEACHING ENGLISH VOCABULARY AT THE JUNIOR HIGH SCHOOL - Habi Septiawan; Khairun Nisa; Uswatun Hasanah; Sudirman Husin (FKIP Universitas Lampung, 2021)
The purpose of this study was to find differences in students' vocabulary before and after being taught using the reverse spelling game technique. This study shows that students taught by reverse spelling games give a more relaxed and interesting impression on vocabulary learning. The initial test score is 57.19 while the final test score is 79.30. The results of the assessment of the initial and final exams, it was found that there was a very important difference, the group assessment of the student's improvement was 22.10 after being taught. The total number of all students' correct answers for the 3 elements used (noun, verb, adjective) in the initial test was 570 while the final test was 874. So, the increase was 304. Tujuan penelitian ini adalah untuk menemukan perbedaan vocabulary siswa sebelum dan sesudah diajarkan dengan menggunakan teknik permainan pengejaan terbalik. Penelitian ini menunjukkan bahwa siswa diajarkan dengan permainan pengejaan terbalik memberi kesan lebih santai dan menarik pada pembelajaran vocabulary. Skor penilaian tes awal adalah 57.19 sedangkan ketika skor penilaian pada ujian akhir adalah 79.30. Hasil penilaian ujian awal dan akhir, ditemukan bahwa ada perbedaan yang sangat penting, penilaian kelompok peningkatan siswa 22.10 setelah diajarkan. Jumlah total semua jawaban siswa yang benar untuk 3 unsur yang dipakai (noun, verb, adjective) di test awal 570 sedangkan ketika ujian akhir adalah 874. Jadi peningkatannya dalah 304. Key Words: backward spelling, increasing, vocabulary achievementDOI: http://dx.doi.org/10.23960/Kata.v9.i2.202108